2021
DOI: 10.3390/polym13050810
|View full text |Cite
|
Sign up to set email alerts
|

Polyamide 12 Materials Study of Morpho-Structural Changes during Laser Sintering of 3D Printing

Abstract: The polyamide (PA)-12 material used for additive manufacturing was studied in aspects of morphology and their structural properties for basic stages received during 3D laser printing. Samples were real, big-scale production powders. The structure of polymer was evaluated from the crystallinity point of view using XRD, FTIR, and DSC methods and from the surface properties using specific surface evaluation and porosity. Scanning electron microscopy was used to observe morphology of the surface and evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 22 publications
(25 reference statements)
6
38
0
Order By: Relevance
“…Selective laser sintering (SLS), a variant of powder bed fusion and widely used AM technique, is a process used to produce objects from powdered materials using one or more lasers to selectively fuse the particles at the surface, layer upon layer, in an enclosed chamber [ 57 , 105 , 106 , 107 , 108 ]. The powders can be fused together with different particle binding mechanisms namely solid-state sintering, chemically induced binding, liquid phase sintering (partial melting), and full melting [ 109 ].…”
Section: Printing Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective laser sintering (SLS), a variant of powder bed fusion and widely used AM technique, is a process used to produce objects from powdered materials using one or more lasers to selectively fuse the particles at the surface, layer upon layer, in an enclosed chamber [ 57 , 105 , 106 , 107 , 108 ]. The powders can be fused together with different particle binding mechanisms namely solid-state sintering, chemically induced binding, liquid phase sintering (partial melting), and full melting [ 109 ].…”
Section: Printing Processmentioning
confidence: 99%
“…Print parameters can be grouped as machine parameters and process parameters for each printing technique (Figure 3). Selective laser sintering (SLS), a variant of powder bed fusion and widely used AM technique, is a process used to produce objects from powdered materials using one or more lasers to selectively fuse the particles at the surface, layer upon layer, in an enclosed chamber [57,[105][106][107][108]. The powders can be fused together with different particle binding mechanisms namely solid-state sintering, chemically induced binding, liquid phase sin- The machine parameters for FDM printing are bed calibration and nozzle diameter while the process parameters are nozzle temperature, bed temperature, extrusion width, and raster angle [52,97], see Figure 3 (left) for the schematic illustration.…”
Section: Printing Processmentioning
confidence: 99%
“…Additive manufacturing (AM) is gaining increasing importance in industry, not just as a technology for prototyping, but also, and in most cases, for production of functional parts in various fields. Polyamides, or nylons, were the first materials to be recognized as engineering thermoplastics, owing to their superior mechanical properties (especially when exposed to elevated temperatures or solvents) [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the bands at 1464 and 1159 cm À1 were due to C H bending and C N stretching. Touris and coworkers 41 and Simha et al 42 showed similar spectra for PA12 in their studies.…”
Section: Ftir Spectra Analysismentioning
confidence: 52%